Manipulation of anchoring strength in an azo-dye side chain polymer by photoisomerization - Thieghi, L. T.; Barberi, R.; Bonvent, J. J.; Oliveira, E. A.; Giacometti, J. A. [UNESP]; Balogh, D. T. (American Physical Society (APS), 2003)
The generation of surface anisotropy by photochemical means has been proposed as an attractive method to align liquid crystals. In this paper, we present an experimental study of the alignment induced on a liquid crystal by a polymer film containing azo-dye groups in the side chain. Optical measurements were performed in nematic liquid crystal cells to determine the azimuthal and zenithal anchoring strengths as a function of the irradiation energy and chromophores concentration. It was observed that the director tends to align perpendicular to the polarization direction of the incident light and the orientation process consists essentially of a rotation of the director in the plane parallel to the boundary surfaces. However, the concentration of azo-dye groups in the polymer film must exceed a minimum value to get a macroscopical effect on the liquid crystal alignment. It is shown that the azimuthal anchoring strength can be varied two orders of magnitude by controlling the irradiation energy and azo-dye concentration. © 2003 The American Physical Society.